2016
DOI: 10.1002/2016tc004244
|View full text |Cite
|
Sign up to set email alerts
|

Orogen‐parallel deformation of the Himalayan midcrust: Insights from structural and magnetic fabric analyses of the Greater Himalayan Sequence, Annapurna‐Dhaulagiri Himalaya, central Nepal

Abstract: The metamorphic core of the Himalaya (Greater Himalayan Sequence, GHS), in the Annapurna‐Dhaulagiri region, central Nepal, recorded orogen‐parallel stretching during midcrustal evolution. Anisotropy of magnetic susceptibility and field‐based structural analyses suggest that midcrustal deformation of the amphibolite facies core of the GHS occurred under an oblate/suboblate strain regime with associated formation of low‐angle northward dipping foliation. Magnetic and mineral stretching lineations lying within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 134 publications
(284 reference statements)
1
29
0
Order By: Relevance
“…The magnetic susceptibility of the Pengguan granitic rocks mostly arises from paramagnetic biotite and partly ferromagnetic magnetite (PSD or MD) based on Km , thermomagnetic, hysteresis loop, and isothermal remanent magnetization measurements. Numerous previous studies have demonstrated that paramagnetic minerals and ferromagnetic minerals carry comparable magnetic fabrics with the mineral petrofabrics in terms of orientation (Borradaile & Jackson, ; Bouchez & Gleizes, ; Bouchez et al, ; Parsons, Ferré, et al, ; Rochette et al, ]. Stereonet projection and microscopic characteristics indicate that the well‐clustered magnetic fabrics of the mylonitic samples within the Pengguan complex are consistent with the field observed fabrics (Figures b, S2a, and S2b).…”
Section: Anisotropy Of Magnetic Susceptibility (Ams) and Petrofabric supporting
confidence: 72%
See 1 more Smart Citation
“…The magnetic susceptibility of the Pengguan granitic rocks mostly arises from paramagnetic biotite and partly ferromagnetic magnetite (PSD or MD) based on Km , thermomagnetic, hysteresis loop, and isothermal remanent magnetization measurements. Numerous previous studies have demonstrated that paramagnetic minerals and ferromagnetic minerals carry comparable magnetic fabrics with the mineral petrofabrics in terms of orientation (Borradaile & Jackson, ; Bouchez & Gleizes, ; Bouchez et al, ; Parsons, Ferré, et al, ; Rochette et al, ]. Stereonet projection and microscopic characteristics indicate that the well‐clustered magnetic fabrics of the mylonitic samples within the Pengguan complex are consistent with the field observed fabrics (Figures b, S2a, and S2b).…”
Section: Anisotropy Of Magnetic Susceptibility (Ams) and Petrofabric supporting
confidence: 72%
“…Magnetic susceptibility ( K ) is the ratio of the induced magnetization ( M ) of a specimen to the externally applied magnetic field ( H ) (Borradaile & Jackson, , ). The anisotropy of magnetic susceptibility (AMS) is a second rank tensor that describes directional variation of a specimen's magnetic susceptibility, which can be used as deformation proxy if the contributing factors (mineral content, mineral shape fabric, and crystallographic fabric) are determined (Borradaile & Jackson, , ; Kruckenberg et al, ; Parsons, Ferré, et al, ). The AMS is geometrically represented by an ellipsoid defined by three orthogonal principal axes, K 1 (maximum), K 2 (intermediate), and K 3 (minimum) (Tarling & Hrouda, ).…”
Section: Anisotropy Of Magnetic Susceptibility (Ams) and Petrofabric mentioning
confidence: 99%
“…At a few localities in the middle of the GHS, the quartz and biotite aggregate lineation is subparallel to the strike of the foliation and trends east‐west. Elsewhere in Nepal Himalaya, east‐west trending mineral lineations have been interpreted to reflect orogen‐parallel flow (e.g., Parsons et al, ; Pêcher, ). Top‐to‐the‐SW shear‐sense indicators are abundant in the MCT high‐strain zone and sparse above it.…”
Section: Geology and Structure Of The Karnali Klippementioning
confidence: 99%
“…Ruddiman, Raymo, Prell, & Kutzbach, ; Zhisheng, Kutzbach, Prell, & Porter, ). Formation of the graben has alternatively been described as a consequence of expansion of the Himalayan arc (Klootwijk, Conaghan, & Powell, ; Seeber & Armbruster, ), oblique convergence between India and Asia (McCaffrey & Nabelek, ) possibly with an oblate strain component (Parsons et al, ), oroclinal bending (Ratschbacher, Frisch, Liu, & Chen, ), or a far field manifestation of wide‐scale Neogene extension that affects much of SE Asia (Yin et al, ). Regardless of the specific mechanism, the cessation of the South Tibetan detachment system and subsequent initiation of E‐W striking graben represents a first order shift in orogen‐scale kinematics.…”
Section: Introductionmentioning
confidence: 99%